Metal-insulator transition in correlated systems: A new numerical approach - García, D. J. (2007)
We study the Mott transition in the Hubbard model within the dynamical mean field theory approach where the density matrix renormalization group method is used to solve its self-consistent equations. The DMRG technique solves the associated impurity problem. We obtain accurate estimates of the critical values of the metal-insulator transitions. For the Hubbard model away from the particle-hole symmetric case we focus our study on the region of strong interactions and finite doping where two solutions coexist. In this region we demonstrate the capabilities of this method by obtaining the frequency-dependent optical conductivity spectra. With this algorithm, more complex models having a larger number of degrees of freedom can be considered and finite-size effects can be minimized.